Pengaruh Kecerdasan Numerik dan Minat Belajar Terhadap Hasil Belajar Matematika Siswa - Khoirun Nisak; Dian Septi Nur Afifah (JURNAL PENDIDIKAN MATEMATIKA, 2019)
ABSTRACT. This research is quantitative research with experimental design is a non-eksperimental design. The purpose of this study is to determine the influence of numerical intellegence and interset in learing outcomes of student. Population in this study is the students of class VIII MTs Darussalam, while samples taken are students class VIII B. The variables in this study consist of two kinds of independent variable and dependent variable. Independent variable in this stuy is numerical intellegence and  interset in learning, while the dependept variable is the result of learning mathematics students. Data collection methods use are documentation, questionare and test. The data analysis techniques used are normality test, simple regressio test and multiple regression test. Based on the data it can be conclude that (1) there is influence of numerical intellegence on student learning result of mathematics, (2) there is an influence of interest in learning on student’s mathematics learning outcomes, (3) there is an influence of numerical intellegence and interest in learning of mathematics learning outcomes.   Keywords:numerical intellegence, interest in learning, learning outcomes mayhematics.